2017
DOI: 10.1016/j.japh.2017.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacy-based statewide naloxone distribution: A novel “top-down, bottom-up” approach

Abstract: A multi-pronged approach coupling state and community collaboration was successful in overcoming barriers and challenges associated with pharmacy naloxone distribution and ensured its success as an effective avenue for naloxone acquisition in urban and rural communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
50
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 8 publications
0
50
0
Order By: Relevance
“…Five studies examined training and education programs for practicing pharmacists. 45,[47][48][49][50] State-mandated training requirements were reviewed for pharmacists dispensing naloxone in states where the legislatures permitted enhanced access to naloxone through pharmacies. 47 To date, all states except Nebraska have enhanced pharmacy naloxone access laws, including 43 states with standing orders and 14 state with protocol orders.…”
Section: Programs For Practicing Pharmacistsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five studies examined training and education programs for practicing pharmacists. 45,[47][48][49][50] State-mandated training requirements were reviewed for pharmacists dispensing naloxone in states where the legislatures permitted enhanced access to naloxone through pharmacies. 47 To date, all states except Nebraska have enhanced pharmacy naloxone access laws, including 43 states with standing orders and 14 state with protocol orders.…”
Section: Programs For Practicing Pharmacistsmentioning
confidence: 99%
“…In New Mexico, the initiation of a statewide standing order and standardized training program resulted in a 9-fold increase in naloxone dispensing by pharmacists. 50 In Kentucky, participation in a 90-minute inperson or online webinar training on naloxone access and dispensing, opioid overdose, and identifying patients at risk allowed pharmacists to register as a "naloxone-certified pharmacist" with the state board of pharmacy. 49 As a result, a large number of pharmacists and student pharmacists were trained and about half of trained pharmacists became certified.…”
Section: Programs For Practicing Pharmacistsmentioning
confidence: 99%
“…Many pharmacists have recognized this position and pharmacy-based programs to address the opioid crisis have been initiated. Identifying naloxone-eligible patients and implementation of naloxone distribution programs are 2 examples 8,9 A recent analysis of state-level changes related to naloxone-dispensing laws revealed that the states that granted direct authority to pharmacists to provide naloxone saw significant reductions in fatal opioid overdoses, whereas the other states did not. 10 Programs that go beyond naloxone distribution and incorporate multipronged pharmacist-led approaches to reducing opioid risk, including increasing availability of medication take-back locations and focused patient education, have also been described.…”
mentioning
confidence: 99%
“…Given the S‐shaped implementation curve—e.g. 187% increase in individuals equipped with naloxone by overdose prevention programs when comparing the first 14 years of implementation to the next 4 years (53 032 from 1996 to 2010; 99 251 from 2010 to 2014) , and that naloxone distribution to individuals prescribed opioids is relatively new , we should expect to see more dramatic increases in naloxone reports to US poison centers in the future.…”
mentioning
confidence: 99%